Identification, localization and differentiation of erosions and physiological bone channels by ultrasound in rheumatoid arthritis patients - Finzel, Stephanie; Aegerter, Philippe; Schett, Georg; D'Agostino, Maria-Antonietta (Rheumatology, 2020)
Objectives. Ultrasound (US) can detect cortical bone lesions in RA. However, not all cortical bone lesions are erosions. Herein, we aimed to define whether US can differentiate between physiological bone channels and pathological erosions in RA and to provide topographic description of their differential localization.
CRIS-Team WoS Importer:2021-01-29